Essentials of ophthalmology: for medical school and beyond : textbook - Manotosh, R. Ray; Koh, V. Victor (Part of the NUHS textbook series, 2019)
Essentials of ophthalmology for medical school and beyond. Written by multi-disciplinary faculty of the Department of Ophthalmology, National university health system (Singapore), Essentials of Ophthalmology: Medical school and beyond is a reference book for the medical undergraduates and residents but the contents will also benefit family physicians who really are the first line of eye-care givers in the community. The authors constantly asked themselves "how much is too much" and deliberately attempted to weed out any "excess" for the benefit of the target readers. The content is written in a point format with lucid language that is supplemented with more than 200 high resolution clinical pictures and illustrations. Emphasis has been focused on information that constitutes essential ophthalmic "core conditions and problems" of the current medical undergraduate curriculum. Every section in the book has "learning objectives" and a "take home message" to facilitate quick learning. The book embraces a practical guide to the study of ocular diseases, basic methods of investigations and treatment where applicable.